Computer simulation of metal-ion equilibria in biochemical systems : models for blood plasma - May, Peter Michael (Department of Chemistry, 2016)
This thesis describes an investigation, by computer simulation, into the nature of the metal ion binding to low molecular weight ligands in blood plasma. A successful attempt is made to accommodate the effects of metal protein binding on the computed distribution that is obtained. An evaluation of the results is undertaken. The value and some applications of the knowledge arising from this kind of study are examined. The collection, assembly and processing of the data is described. A computer program is written to cope with the very large equilibrium systems that are simulated. The experimentally determined values for the formation constants of the metal ion ligand complexing reactions in the biofluid are found in the literature. These are corrected whenever they are not applicable to physiological conditions of temperature and ionic strength. Where no experimental values were available, formation constants for complexes that seemed likely to be important were estimated using certain types of chemical trend. The results of the blood plasma model may be summarized as follows. Copper and ferric iron are found to exist exclusively as ternary complexes except that the copper dihistidinato complex is important. With copper, these ternary complexes always involve histidine whilst citrate plays an analogous role in the ferric complex formation. Calcium, magnesium and manganese do not appear to exist as ternary complexes. With these three cations the bicarbonate species predominate although the binding is weak; as a consequence of the relatively high ligand concentration in plasma. Zinc and lead form both binary and ternary complexes. The ternary zinc cysteinate citrate complex is found to account for a significant percentage of the low molecular weight complex fraction of this metal. This result is in contrast to those of previous models.